Consultation and Cross-professional Collaboration to Resolve Students' Problem Behaviors: An Action Research - Su-Fen Tu (National Taipei University of Education, 2018)
This action research explored the consultation process of a counseling psychologist who worked collaboratively with a teacher to resolve her difficulties with students' behavioral problems. The researcher served as a consultant, while the consultee was a 26-year-old female novice teacher. The research followed the "question-action-evaluation" process, the action plan comprised of four days of training, ten classroom sessions and five teacher consultation session. The results showed that there were five major process factors and a "positive support and interpersonal feedback centered teacher consultation model" was conceptualized. The model suggested that providing positive support and interpersonal feedback to the teacher was the key factor in consultation. Other factors included to explore and assess, to understand the meaning of client and system's behavior, to develop positive behavior support guidance strategies, and to obtain teacher's awareness and insight. Additional important findings were that consultation involved cross-professionals' collaboration during which consultant introduced "others" perspective but respected teacher's subjectivity. Also, having considerations of individual, class dynamics and teacher-students' relationships was necessary for developing appropriate guidance strategies. Actions of changes were initiated when the teacher's self-awareness was enhanced. With a focus on teacher's strengths and positive supports during the consultation, the teacher grew and transferred the positive experience to the students. Finally, the current research provided discussion and suggestions about teachers' anxieties and challenges in resolving students' problem behaviors under traditional Chinese teachers' culture.